PENGARUH PELATIHAN âPENGASUHAN IBU CERDASâ TERHADAP STRES PENGASUHAN PADA IBU DARI ANAK AUTIS - , FINA HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Past research has shown that parents of children with autism had the highest parenting stress than parents of children with other disabilities. This study aims to determine the effect of training "pengasuhan ibu CERdaS" of parenting stress in mothers of children with autism. The study subjects were 20 mothers of children with autism who experience parenting stress from midle to high category, which is divided into an experimental group and control group. The experimental group were 10 people, and the control group are 10 people (waiting list). Training " pengasuhan ibu CERdaS " `was given by 7 sessions in the twice meetings. Parenting stress was measured using a scale of PSI (Parenting Stress Index) before being given the training (pretest), administered after training (posttest), and a week after treatment (follow-up). quantitative analysis using statistical techniques of analysis Wilcoxon signed rank (non-parametric) to measure the differences between two samples. Based on quantitative data analysis of pretest and posttest measurements of the experiment for the group: the value of Z = - 2.499 and 0.012 significance level (p <0.05), indicating a significant decrease in parenting stress in the experimental group after the training is given. Thus training "pelatihan ibu CERdaS" could statistically reduce parenting stress in mothers of children with autism.